Study of serial readout device of time-based CMOS image sensor design - Cai, Weifan (2015)
This project is aimed to design a fast serial readout device that adopts a combined absolute address coding (AAC) and relative address coding (RAC) methods. A logic configuration is created following the methods and a group of PISO shift registers are connected. A control circuitry is another important part of the project, which processing the mixed signals from other blocks. It is a communication bridge between different blocks. A simulation test is taken on the integration of each blocks that consists of 4×15 pixels array .Finally, an analysis of the adaptive address coding method is performed.